OBSERVATIONS ON SOME ASPECTS OF BIOLOGY OF THREADFIN BREAM NEMIPTERUS MESOPRION (BLEEKER) FROM KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
The length-weight rela*k>nisihiip of N. mesoprion can be described by theequation log W = -4.650901 + 2J877071 log L. Feimafes attain first maturity ata length of 100 mm. Thfe species is a fractiiioinial spawner, releasing the ripe ovain two spawning acts editing the Single spawndlng season: December-April. It isestimated that the species attains 140, 1*5 and 205 mm at the completion of first,second and third years, respectively. The estimated growth parameters are: L